Integrating the PLUS-InVEST Model to Project Water Conservation Dynamics and Decipher Climatic Drivers in the Chengdu–Chongqing Economic Zone Under Multiple Future Scenarios - Kangwen Zhu; Suqiong Li; Wei Huang; Peng Hou; Yaqun Liu; Jian Liu; Zihui Li (Hydrology)
Identifying the evolutionary trends of water conservation functions and their climatic impacts under future scenarios is crucial for enhancing regional ecological security. This study integrates the PLUS and InVEST models with projected land use and meteorological data to analyze water conservation patterns in the Chengdu–Chongqing Economic Zone during 2030–2050 under natural development (ND) and ecological protection (EP) scenarios. Key findings include the following: (1) during 2000–2020, low-value areas decreased from 60% to 40%, while high-value zones expanded from 27.32% to 40.35%; (2) both the ND and EP scenarios project lower water conservation volumes compared to 2020 levels; (3) under the ND scenario, the combined proportion of high and extreme importance zones fluctuates at 0.51% (2030), 0.11% (2040), and 3.97% (2050); (4) spatial heterogeneity shows high-value clusters concentrated in Chengdu’s urban core and northeastern regions, contrasting with midland low-value areas; (5) the SSP1-1.9 climate scenario yields higher water conservation capacity with stronger spatial aggregation compared to SSP2-4.5. This integrated modeling of PLUS and InVEST provides scientific support for regional ecological security and sustainable development strategies.